Developing Vocabulary in Second Language Acquisition through Theories to the Classroom (Individual Differences in SLA) - Dai, Sri Oktavia; Paputungan, Nursiti Aisyah (British (Jurnal Bahasa dan Sastra Inggris), 2024)
This research explores the development of vocabulary in second language acquisition (SLA) by examining how individual differences influence language learning processes. The study synthesizes various theoretical frameworks, including cognitive, sociocultural, and psycholinguistic approaches, and their application in the classroom. By focusing on individual learner characteristics such as motivation, cognitive styles, age, and affective factors, the research aims to understand how these differences shape vocabulary acquisition. The method of this research is a qualitative method using thematic analysis. The results of this study reveal that although SLA theories provide a solid foundation for second language teaching, success in vocabulary acquisition is greatly influenced by factors such as motivation, learning strategies, and cognitive abilities possessed by individual students. Therefore, an understanding of individual differences is crucial in designing effective teaching methods.Keywords: SLA, vocabulary acquisition, teaching.